A1E reduces stemness and self-renewal in HPV 16-positive cervical cancer stem cells. Issue 1 (December 2015) - Kwon, Taeho; Bak, Yesol; Ham, Sun-Young; Yu, Dae-Yeul; Yoon, Do-Young
Abstract Background Cervical cancer is the second most common cancer in females. Recent reports have revealed the critical role of cervical cancer stem cells (CSCs) in tumorigenicity and metastasis. Previously we demonstrated that A1E exerts an anti-proliferative action, which inhibits the growth of cervical cancer cells. Methods A1E is composed of 11 oriental medicinal herbs. Cervical cancer cell culture, wund healing and invasion assay, flow cytometry, sheroid formation assay, and wstern blot assays were performed in HPV 16-positive SiHa cell and HPV 16-negative C33A cells. Results A1E targets the E6 and E7 oncogenes; thus, A1E significantly inhibited proliferation of human papilloma virus (HPV) 16-positive SiHa cells, it did not inhibit the proliferation of HPV-negative C33A cells. Accordingly, we investigated whether A1E can regulate epithelial-to-mesenchymal transition (EMT), CSC self-renewal, and stemness-related gene expression in cervical cancer cells. Down rgulation of cell migration, cell invasion, and EMT was observed in A1E-treated SiHa cells. Specifically, A1E-treated SiHa cells showed significant decreases in OCT-3/4 and Sox2 expression levels and in sphere formation. Moreover, CSCs makers ALDH+ and ALDH, CD133 double positive cell were significantly decreased in A1E-treated SiHa cells. However, A1E treatment did not down regulate ALDH+ expression and the number of ALDH/CD133 double positive cells in C33A cells. Conclusions Taken together, A1E can inhibit CSCs and reduce the expression of stemness markers. Treating CSCs with A1E may be a potential therapy for cervical cancer.